Aggregatibacter actinomycetemcomitans Outer Membrane Proteins 29 and 29 Paralogue Induce Evasion of Immune Response - Silva, Maike Paulino da; Silva, Viviam de Oliveira; Pasetto, Silvana; Ando-Suguimoto, Ellen Sayuri; Kawamoto, Dione; Mata, Gardênia Márcia Silva Campos; Murata, Ramiro Mendonça; Mayer, Marcia Pinto Alves; Chen, Casey (Frontiers in Oral Health, 2022)
A. actinomycetemcomitans (Aa) is abundant within the microbial dysbiotic community of some patients with periodontitis. Aa outer membrane protein 29 (OMP29), a member of the OMPA family, mediates the invasion of Aa to gingival epithelial cells (GECs). This study evaluated the effect of OMP29 and its paralogue OMP29par on the response of GECs to Aa. The omp29 or/and omp29par deletion mutants AaΔ29, AaΔ29P and AaΔ29Δ29P were constructed, and recombinant Aa OMP29His was obtained. Microarray analysis and the evaluation of cxcl-8 gene expression were performed to examine the response of GECs line OBA-09 to Aa and its mutants. The expression of cxcl-8 and its product CXCL-8 was examined in LPS-stimulated OBA-09 cells with Aa OMP29His. Proteomics analysis showed that the deletion of omp29 led to overexpression of both OMP29par and another membrane protein OMP39, the expression of which was further increased in AaΔ29Δ29P. OBA-09 cells challenged with AaΔ29Δ29P exhibited a higher expression of cxcl-8 in comparison to wildtype Aa strain AaD7S or single-deletion mutants AaΔ29 or AaΔ29P. LPS-stimulated OBA-09 cells challenged with Aa OMP29His showed reduced expressions of cxcl-8 and its product CXCL-8. OBA-09 cells challenged with AaΔ29Δ29P in comparison to Aa strain AaD7S resulted in higher expressions of genes involved in apoptosis and inflammatory response such as bcl2, birc3, casp3, c3, ep300, fas, fosb, grb2, il-1a, il-1β, il-6, cxcl-8, nr3c1, prkcq, socs3 and tnfrsf1β and reduced expressions of cd74, crp, faslg, tlr1, and vcam1. The results suggested a novel strategy of Aa, mediated by OMP29 and OMP29par, to evade host immune response by inhibiting CXCL-8 expression and modulating the genes involved in apoptosis and inflammatory response in GECs. Pending further confirmation, the strategy might interfere with the recruitment of neutrophils and dampen the host inflammatory response, leading to a more permissive subgingival niche for bacterial growth.